Penggunaan Metode Inquiri untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS pada Siswa Kelas IV SD - Abdullah, Aleyda (Jurnal Bimbingan dan Konseling Terapan, 2017)
The research that will be carried out is aimed to know the use of inquiri method can improve student learning outcomes in IPS subjects in class IV SD Negeri 5 Ambon. This research is a qualitative research with type of classroom action research. The subjects of this study are the students of grade IV (four) SD Negeri 5 Ambon Nusaniwe Subdistrict, which amounted to 35 students. Data were collected with observation sheets. In the study of this class action is used qualitative description analysis, this analysis is calculated by using simple statistic. In the initial test students who score ≥ 65 as many as 57.14% of students, after the first cycle increased to 73.50% students. The average initial test score of 30.85% and after the first cycle increased to 71.14%. On the second cycle also increased the students who get the value of ≥ 65 as many as 81.76% of students. The average value of the end test of cycle II increased to 81.14%.